Thraulodes basimaculatus sp. n., a new species of mayfly from Bolivia: (Ephemeroptera: Leptophlebiidae: Atalophlebiinae) - Giordano, José A.; Domínguez, Eduardo (Zootaxa, 2005)
Thraulodes basimaculatus n. sp. is described from male imagos from Alto Beni, Bolivia. The males of this species present the unique characteristic of having most of the basal half of the fore wings and the entire membrane of the hind wings stained with brown. No other Thraulodes species has similar coloration.